The Impact of Occupational Health and Safety (OHS) and Compensation on Employee Performance at Fuji Mandiri Paving Block Factory, Bogor - Hardiansyah, Rafli; Suroto, Suroto (Transforma Jurnal Manajemen, 2025)
This study aims to analyze the effect of occupational health and safety (OHS) and compensation on employee performance at the Fuji Mandiri Paving Block Factory in Bogor, both partially and simultaneously. This study uses a saturated sample technique with 63 employees as respondents. Data were collected through primary and secondary sources, then analyzed using descriptive statistical tests, classical assumption tests, simple and multiple linear regression analysis, and hypothesis tests (t-test and F-test). The results of the study indicate that partially, OHS has a positive and significant effect on employee performance with a regression equation of Y = 17.245 + 0.632X? and a calculated t value of 3.374> t table 1.67022 (sig. 0.001 <0.05). Compensation also has a positive and significant effect with the equation Y = 9.608 + 0.790X? and a calculated t value of 6.602> t table 1.67022 (sig. <0.001 <0.05). Simultaneously, K3 and compensation have a significant effect on employee performance with the equation Y = 7.331 + 0.265 X? + 0.580 X?, correlation value of 0.861, determination coefficient of 74.2%, and F count value of 86.261 > F table 3.150 (sig. <0.001 <0.05).